Chemical and mineral composition of Pleurotus ostreatus cultivated in Mongolia - L, Munkhgerel; L, Enkh-Amgalan; D, Mungunnaran; B, Munkhtsetseg; B, Bayarmaa (Bulletin of the Institute of Chemistry and Chemical Technology, 2018)
This study aimed to compare and evaluate the chemical composition of fruiting body and mycelium from Pleurotus ostreatus (Jake.) P.Kumm) mushrooms cultivating in Mongolia. The result showed that total lipid: 1.73% in the fruiting body, 0.6% in the mycelium. Protein: 25.7% in the fruiting body and 15.1% in the mycelium. Total carbohydrate’s content was similar in fruiting body and mycelium. According to the results of mineral nutrients, elements such as potassium, phosphorus, and magnesium are dominant, and they have accumulated differently in the fruiting body and mycelium of mushroom. For example, potassium was 12030 mg/kg in the fruiting body and 16380 mg/kg in the mycelium. Phosphorus content was 4225.26 mg/kg in the fruiting body and 6645.19 mg/kg in the mycelium, respectively. According to the study, contents of heavy, toxic metals were tolerable level. This study was identified that Pleurotus ostreatus mushrooms are cultivating in our country, it contains a high amount of nutrient elements and suitable for use in dietary supplements. Тарималжуулсан эвэрлэг дэрвээлж (Pleurotus ostreatus) мөөгний химийн найрлага болон эрдэс бодисын судалгаа Хураангуй: Энэхүү судалгааны ажлаар Монгол оронд тарималжуулж буй Эвэрлэг дэрвээлж (Pleurotus ostreatus (Jake.) P.Kumm) мөөгний үрт бие, ургал биеийн химийн ерөнхий найрлагыг харьцуулан судалж үнэлэлт дүгнэлт өгөхийг зорилоо. Тос, тосонцор бодис мөөгний үрт биед - 1.73%, ургал биед нь - 0.6%; уураг үрт биед - 25.7%, ургал биед - 15.1% ба нийт нүүрсусны агууламж ойролцоо байна. Эрдэс бодисын судалгааны дүнгээр кали, фосфор, магни зэрэг элементүүд зонхилж байгаа бөгөөд мөөгний үрт бие болон ургал биед харилцан адилгүй хуримтлагддаг байна. Тухайлбал, кали: үрт биед – 12030 мг/кг бол ургал биед- 16380 мг/кг; фосфор: үрт биед - 4225.26 мг/кг, ургал биед 6645.19 мг/кг тус тус агуулагдаж байна. Судалгаанд хамрагдсан Эвэрлэг дэрвээлж мөөгөнд хүнд хортой элементүүдийн агууламж хүлцэх хэмжээнд байгааг тогтоов. Эдгээр дүн нь манай оронд тарималжуулан ургуулж байгаа Эвэрлэг дэрвээлж мөөг тэжээллэг чанар сайтай, хүнс болон зохицуулах үйлчилгээтэй хүнсний нэмэлт болгон хэрэглэхэд тохиромжтойг харуулж байна. Түлхүүр үг: Эвэрлэг дэрвээлж, Pleurotus ostreatus, үрт бие, ургал бие, мөөг